Resident Memory T Cells in Autoimmune Skin Diseases - Ryan, Grace E.; Harris, John E.; Richmond, Jillian M. (Frontiers in Immunology, 2021)
Tissue resident memory T cells (TRM) are a critical component of the immune system, providing the body with an immediate and highly specific response against pathogens re-infecting peripheral tissues. More recently, however, it has been demonstrated that TRM cells also form during autoimmunity. TRM mediated autoimmune diseases are particularly destructive, because unlike foreign antigens, the self-antigens are never cleared, continuously activating self-reactive TRM T cells. In this article, we will focus on how TRMs mediate disease in autoimmune skin conditions, specifically vitiligo, psoriasis, cutaneous lupus erythematosus, alopecia areata and frontal fibrosing alopecia.